2019
DOI: 10.3389/fphar.2019.00332
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine Improves the Cognitive Impairment and Depression-Like Behaviors in a Cuprizone Mouse Model by Alleviating Demyelination and Neuroinflammation in the Brain

Abstract: Growing evidence has implicated that myelin deficits and neuroinflammation are the coexisted pathological features that contribute to the mood swing and cognitive decline in major depressive disorder (MDD) and multiple sclerosis (MS). Therefore, attenuation of neuroinflammation and reduction of demyelination became newly emerging treatment strategies for the mood and cognitive symptoms. Antidepressant venlafaxine has been used in depression and anxiety through its multiple neuroprotective effects. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Therefore, we also demonstrated that anxiety- and depression-like behaviors of CPMS mice were recovered by venlafaxine treatment, which inhibits the 5-HT/noradrenalin synaptosomal uptake [ 40 ]. Venlafaxine also has anti-inflammatory property about abnormal inflammatory responses related to microglia as one of the risk factors causing depressive symptoms [ 41 43 ]. So, we confirmed that Velafaxine reduced microglial activation (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we also demonstrated that anxiety- and depression-like behaviors of CPMS mice were recovered by venlafaxine treatment, which inhibits the 5-HT/noradrenalin synaptosomal uptake [ 40 ]. Venlafaxine also has anti-inflammatory property about abnormal inflammatory responses related to microglia as one of the risk factors causing depressive symptoms [ 41 43 ]. So, we confirmed that Velafaxine reduced microglial activation (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FGF22 is expressed mainly in the skin and brain, and the deletion of endogenous FGF22 induced depression-like behavior, as shown by the FST, TST, and SPT (Williams et al, 2016). Recent studies have reported that FGF21 possesses various pharmacological activities including its antioxidant activity, suppression of apoptosis induced by endoplasmic reticulum stress (Liang et al, 2017), and anti-inflammatory activity Zhang et al, 2019). FGF21 weakly binds heparin and can pass through the blood-brain barrier by simple diffusion (Hsuchou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, mounting evidence has suggested the existence of various additional targets for these neurotransmitter re-uptake inhibitors, which either support the therapeutic effect, or on the contrary trigger adverse events [24][25][26][27]. Examples include the protection of paroxetine against dyskinesia in Huntingtin mutant mice and nigrostriatal neurodegeneration in Parkinson's disease mouse model [28,29], and the venlafaxine-mediated improvement of cognitive impairment and depressive behavior in multiple sclerosis mouse model [30]. Clinical studies have also found that long-term use of SSRIs may delay conversion from mild cognitive impairment to Alzheimer's dementia in individuals with previous depression [31], and citalopram and sertraline treatment can improve anxiety symptoms of patients with generalized anxiety disorder [32].…”
Section: Discussionmentioning
confidence: 99%